Rights or Benefits? The Indian Supreme Court and Criminal Procedure. Issue 1 (June 2019) - Sekhri, Abhinav
This article suggests that the recent decisions by the Indian Supreme Court in Mohan Lal v. State of Punjab, and Varinder Kumar v. State of H.P., are perhaps indicative of a more pervasive trend that stretches back to the dawn of the due process era in Indian law. This trend is one where the Supreme Court is confronted with systemic issues in the criminal process while dealing with petitions brought by singularly oppressed litigants, and it treats the litigation itself as a means to solve the perceived problem. The tool to solve these problem in the criminal process is the creation of new criminal procedure rights through the vehicle of Article 21. In its reformist zeal, scant attention is paid to the several important questions of scope and consequential remedy that are inherent to any notion of rights. Over time though, the Court seems to realise that hard cases make bad law. And when cases involving seemingly undeserving litigants start invoking those procedural rights, the Court signals a retreat and transforms the 'right' into a 'benefit', that it can dole out in only the most deserving cases. This is not a definitive study, but only offers a different perspective to examine the Supreme Court's contribution to the field of criminal procedure.